Strategic Positioning and Competitive Advantage of Selected Multimedia Firms in Kigali, Rwanda - Shiramanyama, Ananias; Akims, Malgit (International Journal of Strategic Management, 2025)
Purpose: To assess the effects of strategic positioning on the competitive advantage of multimedia companies in Rwanda, focusing on selected firms: Tele 10, Azam, and Canal+. Methodology: A cross-sectional research design and a mixed-methods approach were utilized. Data were collected through interviews, surveys, and document review. Employing the purposive sampling method, the study had a sample size of 112 respondents same number as the target population of individuals from three selected Multimedia companies, using the universal sampling method. Findings: The findings reveal that customer-centric strategies significantly enhance operational efficiency, brand reputation, and market share (β = 0.163, p = 0.007). Strategic leadership plays a pivotal role in vision setting, decision-making, and adaptability, driving sustainable growth (β = 0.241, p = 0.002). Product differentiation, through unique content and market segmentation, contributes to brand distinctiveness (β = 0.156, p < 0.001). Continuous improvement emerges as the most critical driver, fostering creativity, technological advancements, and service quality improvements (β = 0.437, p < 0.001). Respondents overwhelmingly emphasized the importance of aligning strategic decisions with customer needs, highlighting the value of feedback-driven improvement and exceptional service delivery. The study demonstrates strong interrelations among the factors, with continuous improvement showing the highest predictive power. The combined influence of the variables explains 89.7% of the variance in competitive advantage (R² = 0.897, F = 227.383, p < 0.001). Unique Contribution to Theory, Practice and Policy: The study offers actionable insights for stakeholders in the multimedia industry, emphasizing the necessity of balancing customer-centric approaches, adaptive leadership, distinct product offerings, and continuous improvement-driven strategies. Competitive success lies in leveraging the synergistic effects of these elements to create sustainable value in a highly dynamic and competitive market environment.